NEWMANN NOAH ANAK LUANG - ANAK LUANG, NEWMANN NOAH (IRC, 2019)
Study shows that ReRAM can retain data without power, consume less power and transfer data at a faster rate in comparison with conventional memory technology. More work is put into the development of ReRAM due to rapid growth of technology, limitation of memory space, as well as computer memory endurance cycle. This paper provides a brief introduction of the research. This project aims to develop ReRAM using the sol-gel method and spin coating method. First, ZnO solution is prepared by using sol-gel method in which zinc acetate dihydrate is mixed with solvent and stirred with a magnetic stirrer. Then, the solution is deposited on the Si substrate to develop ZnO thin films by using spin coating method. For characterization of IV curve and physical attributes, SIM2RRAM software was used. The result was, the stable of resistance switching depend on stable reset voltage. While reset voltage is associated with the thickness of Conducting Filament (CF).